The social impacts of trade liberalisation - Pereznieto, P (2005)
The social impacts of trade liberalisation must be considered from a child-sensitive perspective. Trade liberalisation is likely to have a major impact on the lives of children and their families, particularly since children comprise a significant proportion of the population in developing countries. Furthermore, these impacts have been shown to vary between families and children of different genders, ages, economic backgrounds, and localities. Developing countries must pay attention to these different impacts in order to mitigate possible inequities. In this paper, the authors identify the different mechanisms through which trade liberalisation affects household well-being, and the intra-household decision-making mechanism that mediate impacts on children. The findings are based on Young Lives research in Ethiopia and Peru. Ethiopia is preparing to accede to the World Trade Organisation in 2008, and while the short-term impacts of liberalisation may produce some negative impacts, the long-term effects are likely to be positive. In Peru, a free-trade agreement with the United States is likely to have markedly varied impacts across different sectors of the economy and geographic regions, although overall long-term effects are expected to be positive. The authors here consider the consequences of these developments to assess areas where policy interventions will be needed to ensure that trade liberalisation translates into poverty reduction and pro-child benefits. They distinguish between trade-related and non trade-related policies: those that can help mitigate the negative consequences and take advantage of the positive short-term effects of trade liberalisation; and those that compensate for the differential impact of liberalisation on individuals within the family to ensure more equitable results.